STUDENTS AID SYSTEM BASED ON THE FOUR BRAHMAVIHĀRA - Jindasawad, Wassana (Journal of Bovorn Multi-Education and Human Social Sciences ( JOB_EHS ), 2022)
This article presented students aid system based on the four Brahmavihāra principles with two main components: 1) student aid system as it was a step-by-step process of taking care and helping students, including getting to know each student individually, student screening, student promotion and development, preventing, helping and correcting students and students passing, 2) integrating the four Brahmavihāra principles with student aid for administrators and teachers to apply, namely: (1) Mettā, loving-kindness, wishing students to be happy, having a good mind which was friendly and thinks to benefit them, (2) Karuṇā, compassion, cares for the relief of the student's suffering and difficulties, (3) Muditā, sympathetic joy, the joy of the student's well-being, feeling of pleasure towards happy students, (4) Upekkhā, equanimity, not inclined to love and hate, know how to trust correctly.